Answer:
AAA (Or even just two angles work too, since the last has to be the same no matter what) ASA and SSS
Step-by-step explanation:
I believe this is the same as before? As far as I know these are the main rules for proving similarity. (AAS and A** do not exist (Brainly won't let me say the two Ss), make sure no trick questions get you ;p)
I'm not sure if what you needed earlier was the relationships between angles to find them? Like to find Exterior Angles subtract <C from 180 = <EA?
$2.50
Hope this helps!
May I have brainliest? :D
Answer:
![x=5](https://tex.z-dn.net/?f=x%3D5)
Step-by-step explanation:
<u>Similar Triangles</u>
By looking at the construction of the figure, we can safely assume both triangles are similar, i.e. their internal angles are equal and their sides are proportional. Following the proportion of the heights and bases of both triangles we can set this relationship:
![\displaystyle \frac{45}{36}=\frac{5x}{20}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B45%7D%7B36%7D%3D%5Cfrac%7B5x%7D%7B20%7D)
Simplifying both fractions
![\displaystyle \frac{5}{4}=\frac{x}{4}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B5%7D%7B4%7D%3D%5Cfrac%7Bx%7D%7B4%7D)
Solving for x
![x=5](https://tex.z-dn.net/?f=x%3D5)
Answer:
C a1= -2
an = an-1 +3
Step-by-step explanation:
an = -2+ (n-1)3
What is the first term? Let n=1
a1 = -2 + 0*3
a1 = -2
The difference between the terms is +3 (coefficient on (n-1))
The second term is the first term +3
The third term is the second term plus 3
The next term is the previous term +3
so an = an-1+ 3
Answer:
The simplified form of r^-7 + s^-12 is ----> 1/r^7 + 1/s^12
Step-by-step explanation: